Crystallinity characterization method and preparation method of ceramic-based composite material boron nitride interface layer

The spin-lattice relaxation characteristic time T1 of isotope B-11 in the boron nitride interface layer was measured by solid nuclear magnetic resonance, which solved the problem of inaccurate characterization of the boron nitride interface layer structure in the prior art, and realized the ceramics Improve the mechanical properties of matrix composites and reduce the detection cost.

CN119470537APending Publication Date: 2025-02-18AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510045041.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art has inaccurate, complex and costly characterization of the interface layer of boron nitride in ceramic matrix composite materials, and cannot effectively quantitatively or semi-quantitatively reflect its crystallinity.

Method used

The spin-lattice relaxation characteristic time T1 of isotope B-11 in the boron nitride interface layer was measured by solid nuclear magnetic resonance method, and the crystallinity of the boron nitride interface layer was determined based on the value of T1.

Benefits of technology

Accurate quantitative characterization of the interface layer of boron nitride of ceramic matrix composite material is realized, the mechanical properties of the material are improved, the detection cost is reduced, and the optimization of the material preparation process is guided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470537A_ABST
    Figure CN119470537A_ABST
Patent Text Reader

Abstract

The invention relates to a crystallinity characterization method and a preparation method of a boron nitride interface layer of a ceramic-based composite material, belongs to the technical field of ceramic-based composite materials, and solves the problems of inaccurate and complicated characterization of the structure of the boron nitride interface layer in the ceramic-based composite material, no unified standard and high cost in the prior art. The method comprises the following steps: measuring spin-lattice relaxation characteristic time T1 of an isotope B-11 in the boron nitride interface layer by adopting a solid nuclear magnetic resonance method, and characterizing the crystallinity of the boron nitride interface layer by adopting T1. The method can accurately reflect the local atomic-scale structure and movement of the boron atomic nucleus of the boron nitride interface layer, and the microstructure of the boron nitride interface layer affects the combination between the tow fiber and the matrix and determines the toughening effect of the tow fiber. According to the method, quantitative characterization of the interface layer structure in the ceramic-based composite material is realized, optimization of a boron nitride interface layer deposition process is effectively guided, and improvement of the performance of the composite material is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of characterization of a boron nitride interface layer of a ceramic-based composite material, and in particular to a method for characterizing the crystallinity of a boron nitride interface layer of a ceramic-based composite material and a method for preparing the same. Background Art

[0002] Continuous strand silicon carbide fiber toughened silicon carbide-based composites (SiC / SiC composites) maintain the advantages of silicon carbide ceramics such as high temperature resistance, oxidation resistance, low density, high thermal conductivity and low thermal expansion coefficient in their matrix, while the continuous strand fiber and interphase layer provide toughening effects, making it have characteristics that traditional ceramic materials do not have, such as no catastrophic damage. Therefore, this type of material has been widely used in fields such as aircraft engines.

[0003] In the existing technology, hexagonal boron nitride (BN) is the most commonly used interface material for SiC / SiC composites for aircraft engines. It can provide a weak interface, avoid strong bonding between bundle fibers and the matrix, and improve the toughening effect. In addition, the service temperature of SiC / SiC composites used for hot end components of aircraft engines is usually 1200℃ or higher. The borosilicate glass phase formed by the boron nitride interface layer at 800℃ can inhibit oxidation. Therefore, the use of a boron nitride interface layer can further increase the service temperature of SiC / SiC composites. Among them, the structure of the boron nitride in the interface layer, especially the crystallinity, has an important influence on the bonding between the bundle fibers and the matrix, and is one of the key factors affecting the mechanical properties of composite materials.

[0004] At present, the main methods for characterizing the interface layer of boron nitride are XRD, TEM, FT-IR or Raman. Among them, the TEM method is prone to damage to the original structure during the sample preparation process, and it is difficult to ensure that the amorphous state seen during the measurement after TEM sample preparation is definitely amorphous; in addition, whether it is to determine the proportion of crystalline areas or calculate the grain size, TEM has a great deal of randomness because the scale that can be observed in a single sample is too small (often only a few dozen square microns for ceramic materials), and the judgment of grain boundaries is very artificial. Therefore, the TEM method is not only labor-intensive, but also has the randomness of sampling and the human nature of judgment, large errors and inaccuracies; the FT-IR method and the Raman method are greatly affected by external interference, and the Raman method can only test surface samples, the test is uneven and incomplete, and it is difficult to grasp the overall performance of the sample; the XRD method is suitable for hexagonal boron nitride powders and blocks with high crystallinity or even close to complete crystallization. As the crystallinity of boron nitride decreases, the area of ​​the (102) peak becomes difficult to measure, and it cannot accurately and quantitatively characterize the degree of crystallization of hexagonal boron nitride, so it cannot be applied to the characterization of the boron nitride interface layer between the hexagonal structure and the chaotic layer structure; if you want to calculate the grain size L by the half-peak width of the X-ray diffraction peak (002) corresponding to the (002) crystal plane of the hexagonal boron nitride unit cell, c , the signal will be very weak because the interface layer with a thickness of several hundred nanometers is too small compared to the fiber with a diameter of more than ten microns, and it will be interfered by the overlapping XRD peaks of the fiber's own components.

[0005] In view of the above problems, it is necessary to quantitatively or semi-quantitatively characterize the structure of the boron nitride interface layer in SiC / SiC composites to promote the optimization of the structure and preparation process of the boron nitride interface layer in order to improve the mechanical properties of SiC / SiC composites. Summary of the invention

[0006] In view of the above analysis, an embodiment of the present invention aims to provide a method for characterizing the crystallinity of a boron nitride interface layer of a ceramic-based composite material and a preparation method thereof, so as to solve at least one of the problems of the prior art in characterizing the structure of a boron nitride interface layer in a ceramic-based composite material, namely, inaccurate, complex, lacking a unified standard, and high cost.

[0007] In a first aspect, an embodiment of the present invention provides a method for characterizing the crystallinity of a boron nitride interface layer of a ceramic matrix composite material, the method comprising: The spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer is measured by solid-state nuclear magnetic resonance method; Determining the crystallinity of the boron nitride interface layer according to the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer; The composite material includes a ceramic matrix and bundled filament fibers dispersed therein, and the boron nitride interface layer is attached to the surface of the bundled filament fibers.

[0008] Furthermore, the structure of the boron nitride interface layer is determined according to the value of the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer, and the crystallinity of the boron nitride interface layer is expressed by the structure of the boron nitride interface layer.

[0009] Further, when T1<0.1s, the boron nitride interface layer has an amorphous structure; When T1 is 0.1-1.5s, the boron nitride interface layer has a turbostratic structure; When T1 is 1.5-100s, the boron nitride interface layer has an incompletely crystallized hexagonal structure; When T1>100s, the boron nitride interface layer has a completely crystallized hexagonal structure.

[0010] Furthermore, the method for measuring the spin-lattice relaxation characteristic time T1 of the isotope B-11 includes: S1: preparing samples of the boron nitride interface layer of the ceramic matrix composite material; S2: collecting a solid nuclear magnetic resonance spectrum of the sample; S3: performing data fitting on the obtained spectrum to obtain the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer.

[0011] Furthermore, the solid-state nuclear magnetic resonance saturation-recovery method was used to measure the spin-lattice relaxation characteristic time T1 of the isotope B-11.

[0012] Furthermore, in step S2, the sample is subjected to magic angle rotation, and the rotation speed of the magic angle rotation is 5-100 kHz; The number of saturation pulses is 50~200, the pulse length is 1~100μm, the interval time is 0.1~10ms, and the waiting time is 1ms~300s.

[0013] In a second aspect, an embodiment of the present invention provides a method for preparing a boron nitride interface layer in a SiC / SiC composite material, the method comprising: (1) Preparing a boron nitride interface layer on the surface of the bundled fiber by chemical vapor deposition or chemical vapor infiltration process; (2) determining the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer; (3) Determine whether the relaxation characteristic time T1 measured in step (2) is within the range of >1.5s: If the conditions are met, continue to use the process described in step (1) to prepare boron nitride on the surface of the bundled fiber; If it does not meet the requirements, first change the process parameters of step (1), including temperature, pressure, and gas flow rate, and then prepare a boron nitride interface layer on the surface of the bundled filament fiber; (4) Repeat steps (2) to (3) until the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer meets the requirements.

[0014] Furthermore, in step (1), the thickness of the boron nitride interface layer is 50 nm-5 μm.

[0015] Furthermore, in step (2), the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer is measured by solid-state nuclear magnetic resonance saturation-recovery method, wherein in the measurement, the sample is subjected to magic angle rotation at a rotation speed of 5 to 100 kHz. The number of saturation pulses is 50~200, and the interval time is 0.1~10ms.

[0016] Furthermore, the bundled filament fibers are bundled filament SiC fibers.

[0017] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: 1. The present invention utilizes the correlation between the spin-lattice relaxation characteristic time T1 of boron-11 (B-11), the isotope with the highest natural abundance of boron element, and the structural order and structural defects of boron nitride, and adopts the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer of the ceramic-based composite material to characterize the crystallinity of the boron nitride interface layer. Compared with the prior art, the present invention realizes the quantitative characterization of the boron nitride interface layer of the composite material; Among them, the microstructure of the boron nitride in the interface layer will affect the bonding between the bundled fibers and the ceramic matrix, determine the toughening effect of the bundled fibers, and thus affect the mechanical properties of the composite material. Characterizing the boron nitride interface layer using the spin-lattice relaxation characteristic time T1 of the isotope B-11 can better control the product quality of the composite material and guide the material preparation process.

[0018] 2. The spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer of the present invention can accurately reflect the atomic-level structure and movement of the local nucleus. For example, in high-crystallinity boron nitride, a large number of boron atoms are in a repeated regular structure, and the movement of boron atoms and nitrogen atoms near each boron atom is mainly lattice vibration, and the local magnetic field changes little; in low-crystallinity turbostratic boron nitride, there are many structural defects around the boron atoms, including not only dislocations, but also amorphous regions, boron atoms that are unsaturated in coordination and easily combined with water molecules, etc., and the atomic movement forms are diversified, and the local magnetic field is full of changes; the result shown in nuclear magnetic resonance is that the boron nitride with higher crystallinity has a longer spin-lattice relaxation characteristic time T1, and T1 decreases with the decrease of crystallinity. The present invention divides the structure of the boron nitride interface layer into three categories: amorphous, chaotic layer and hexagonal according to the length of the spin-lattice relaxation characteristic time T1 of the isotope B-11 of the boron nitride interface layer. Among them, when the spin-lattice relaxation characteristic time T1 of the isotope B-11 is within the range of >1.5s, the boron nitride interface layer can play a good toughening effect in the ceramic-based composite material.

[0019] 3. The inventors of the present invention have studied the use of the spin-lattice relaxation characteristic time T1 of the isotope B-11 to quantify the crystallinity of the boron nitride interface layer. By controlling the process parameters of the solid-state nuclear magnetic resonance method, the spin-lattice relaxation characteristic time T1 of B-11 of the ceramic-based composite material boron nitride interface layer is accurately and quickly obtained, so as to more accurately understand the structure of the interface layer, facilitate the detection of the quality of the composite material product, and guide the material preparation process. The present invention uses the solid-state nuclear magnetic resonance saturation-recovery method to measure the relaxation time and achieve effective control of the rotation speed and pulse interval time of the magic angle rotation.

[0020] 4. The present invention adopts the method of using the spin-lattice relaxation characteristic time T1 of the isotope B-11 to characterize the crystallinity of the boron nitride interface layer of the ceramic-based composite material, accurately and simply quantifies the structure of the boron nitride interface layer, and forms a unified standard for the detection of the boron nitride interface layer of the ceramic-based composite material, so as to effectively guide the optimization of the boron nitride interface layer deposition process, improve the process consistency of the boron nitride interface layer, and thus improve the performance and production efficiency of the composite material.

[0021] 5. In the method for preparing a boron nitride interface layer in a ceramic-based composite material of the present invention, the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer is measured to understand the structure of the boron nitride interface layer, thereby facilitating the adjustment of process parameters to obtain a boron nitride interface layer on the surface of the bundled fiber that meets the requirements.

[0022] In order to avoid the strong bonding between the bundle fibers and the ceramic matrix and affect the toughening effect of the bundle fibers on the matrix, the present invention prepares a boron nitride interface layer on the surface of the bundle fibers, and after the modified bundle fibers are combined with the ceramic matrix, the interface layer is located between the composite fiber and the matrix, thereby improving the interface bonding state and microstructure of the bundle fibers and the ceramic matrix. On the one hand, the strong bonding between the bundle fibers and the ceramic matrix in the composite material is alleviated, and on the other hand, the bundle fibers are protected from damage in the subsequent preparation of the composite material. Therefore, the boron nitride interface layer is called a fiber coating relative to the bundle fibers, and is called an interface layer relative to the composite material as a whole.

[0023] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are only used for the purpose of illustrating specific embodiments and are not to be considered as limiting the present invention. In the entire drawings, the same reference symbols represent the same components; Figure 1 The pulse sequence used in the solid-state nuclear magnetic resonance saturation-recovery experiment of the present invention; Figure 2 A one-dimensional solid nuclear magnetic resonance spectrum of the boron nitride interface layer of the present invention; Figure 3 The peak area integral value or peak value versus waiting time of the NMR spectrum of the boron nitride interface layer deposited at different temperatures The change value and fitting curve of Figure 4 The tensile properties test curves of SiC / SiC composites prepared by using boron nitride interface layers deposited at different temperatures; Figure 5 TEM test images of the boron nitride interface layers 1-3 prepared in Examples 1-3: (a) interface layer 1; (b) interface layer 2; (c) interface layer 3. DETAILED DESCRIPTION

[0025] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0026] Boron nitride has four main crystal structures: hexagonal boron nitride (h-BN), rhombohedral boron nitride (r-BN), cubic boron nitride (c-BN), and wurtzite boron nitride (w-BN). Among them, hexagonal boron nitride is a stable structure under normal pressure, with a graphite-like lamellar structure, and can be used as an interface layer material and lubricating material; turbostratic boron nitride (t-BN) is a thermodynamically non-stable structure produced when the hexagonal boron nitride crystal is not fully developed or due to external factors such as high-energy ball milling, the crystal has a certain degree of disordered arrangement; if even the short-range ordered structure of turbostratic boron nitride is not available, it is called amorphous boron nitride (a-BN). It should be pointed out that there is no obvious boundary between amorphous boron nitride and turbostratic boron nitride, as well as turbostratic boron nitride and hexagonal boron nitride. Turbostratic boron nitride contains certain amorphous regions, and hexagonal boron nitride also has structural defects such as dislocations and sheet bending. The process from amorphous boron nitride to turbostratic boron nitride and then to hexagonal boron nitride is actually a process of continuously improving crystallinity.

[0027] It should be noted that hexagonal boron nitride crystals belong to the hexagonal crystal system. The (002) crystal plane of the unit cell is parallel to the X-axis and Y-axis of the crystal system, and has an intercept of 1 / 2 on the Z-axis, corresponding to the plane formed by the six-membered ring of boron and nitrogen atoms. The ideal interplanar spacing of the (002) crystal plane is 0.333nm. The grain size normal to the (002) crystal plane (vertical to the plane direction) is marked as Lc. In the X-ray diffraction spectrum, different crystal planes have corresponding diffraction peaks. The diffraction peak corresponding to the (002) crystal plane is usually defined as the (002) peak. The peak position (Bragg angle θ) of the diffraction peak reflects the interplanar spacing, and the half-peak width of the diffraction peak reflects the grain size normal to the crystal plane.

[0028] It should be noted that in order to avoid the strong bonding between the bundle fibers and the ceramic matrix and affect the toughening effect of the bundle fibers on the matrix, the present invention prepares a boron nitride interface layer on the surface of the bundle fibers, and after the modified bundle fibers are dispersed in the ceramic matrix, the interface layer is located between the composite fiber and the matrix, thereby improving the interface bonding state and microstructure of the bundle fibers and the ceramic matrix. On the one hand, the strong bonding between the bundle fibers and the ceramic matrix in the composite material is alleviated, and on the other hand, the bundle fibers are protected from damage in the subsequent preparation of the composite material. Therefore, the boron nitride interface layer can be called a fiber coating relative to the bundle fibers, and can be called an interface layer relative to the composite material as a whole.

[0029] It should be noted that the boron nitride used as the interface layer of the ceramic matrix composite material needs to have a graphite-like lamellar structure, short-range order or long-range order, that is, a hexagonal boron nitride interface layer. The structure of the boron nitride interface layer obtained by the existing preparation technology is mainly incompletely crystallized hexagonal boron nitride, and a completely crystallized hexagonal boron nitride interface layer is difficult to prepare.

[0030] At present, the main methods for characterizing the boron nitride interface layer in ceramic-based composites are XRD, TEM, FT-IR or Raman. Among them, the TEM method not only has a large workload, but also has large randomness and human factors, large errors and inaccuracies; the FT-IR method and the Raman method are greatly affected by external interference, and the Raman method can only test surface samples, the test is uneven and incomplete, and it is difficult to grasp the overall performance of the sample.

[0031] Crystallinity is an indicator that reflects the proportion of the crystalline part of a substance, and is mainly used for partially crystalline substances such as ceramics, carbon, and polymers. Based on the structural similarity between hexagonal boron nitride and graphite, although Thomas, J. Jr. et al. proposed the graphitization index of hexagonal boron nitride in 1963, the graphitization index is only applicable to hexagonal boron nitride powders and blocks with high crystallinity or close to complete crystallization, and cannot be applied to the characterization of hexagonal boron nitride interface layers with low crystallinity and incomplete crystallization. The characterization of the boron nitride interface layer exceeds the scope of application of this concept proposed by Thomas, and cannot accurately quantify the crystallinity of the boron nitride interface layer of the ceramic matrix composite material, thereby failing to accurately detect and control the quality of the product, failing to effectively guide the optimization of the preparation process of the boron nitride interface layer, and failing to ensure the consistency of the preparation process of the boron nitride interface layer.

[0032] Therefore, the present invention provides a method for characterizing a ceramic-based composite material having a boron nitride interface layer, the method comprising measuring the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer by a solid-state nuclear magnetic resonance method; Determining the crystallinity of the boron nitride interface layer according to the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer; The composite material comprises a ceramic matrix and bundled filament fibers dispersed therein, the boron nitride interface layer is attached to the surface of the bundled filament fibers, and the boron nitride interface layer contains hexagonal boron nitride.

[0033] It should be noted that for a nuclear spin system with a non-zero spin quantum number, it will split into two or more energy levels under the action of an external magnetic field (Zeeman effect); if the external magnetic field remains constant, the population of the spins at each energy level will eventually satisfy the Boltzmann distribution law, and the nuclear spin system will enter an equilibrium state; applying a radio frequency pulse to the nuclear spin system can cause the nuclear spin to enter an excited state from an equilibrium state; after the pulse ends, the population of the nuclear spin system will undergo a process of Boltzmann distribution from an excited state to an equilibrium state, which is called spin-lattice relaxation.

[0034] It should be noted that a completely isolated spin system can theoretically remain in an excited state, but in reality, the spin system must transfer the energy obtained from the radio frequency pulse to the external environment (lattice) through the changing local magnetic field of the atomic nucleus, and this energy is ultimately converted into the energy of thermal motion of the environmental molecules. Spin-lattice relaxation describes this energy transfer process, and the transfer medium is the changing local magnetic field around the nuclear spin system.

[0035] The inventors found in their research on ceramic-based composite materials that the isotope B-11 spin-lattice relaxation characteristic time T1 in seconds generated by the boron nitride interface layer under the action of an external magnetic field can accurately reflect the microstructure of the boron nitride interface layer, and is related to the structural order and structural defects of boron nitride; and the structure of the boron nitride interface layer will affect the bonding performance between the bundle fiber and the ceramic matrix. Under the same test conditions and preparation conditions, the composite materials prepared by using bundle fibers with boron nitride interface layers with different relaxation characteristic time T1 values ​​on the surface have different mechanical properties, and the crystallinity reflects the degree of crystallization of boron nitride, that is, an indicator of the proportion of the ordered part. Therefore, the present invention uses the isotope B-11 spin-lattice relaxation characteristic time T1 to characterize the crystallinity of the boron nitride interface layer of the ceramic-based composite material, and quantifies the structure of the boron nitride interface layer to accurately detect and control the quality of the product, effectively guide the optimization of the preparation process of the boron nitride interface layer, and ensure the consistency of the preparation process of the boron nitride interface layer.

[0036] It should be noted that for the same material with different crystallinity, molecular motion is the main factor that causes the rapid change in the intensity of the local magnetic field. The inventors found in their research on the crystallinity of the boron nitride in the interface layer that after a pulse is applied to boron nitride, the spin-lattice relaxation characteristic time T1 of the boron isotope boron-11 (B-11) nuclei is correlated with the structural order and structural defects of boron nitride. The spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer of the ceramic-based composite material can accurately reflect the local atomic-level structure and motion of the nuclei, and can characterize the crystallinity of the boron nitride interface layer.

[0037] When the present invention measures the spin-lattice relaxation characteristic time T1 of the boron nitride interface layer B-11, for high-crystallinity boron nitride, a large number of boron atoms are in a repeated regular structure, the movement of boron atoms and nitrogen atoms near each boron atom is mainly lattice vibration, and the local magnetic field changes slightly; for low-crystallinity disordered boron nitride, there are more structural defects around the boron atoms, not only dislocations, but also amorphous regions, boron atoms that are unsaturated in coordination and easily combined with water molecules, etc., the atomic movement forms are diversified, and the local magnetic field is full of changes; the result shown in nuclear magnetic resonance is that the boron nitride with higher crystallinity has a longer spin-lattice relaxation characteristic time T1, and T1 decreases with the decrease of crystallinity.

[0038] Specifically, the present invention uses the spin-lattice relaxation characteristic time T1 in seconds to characterize the crystallinity of hexagonal boron nitride, which is called the crystallinity index.

[0039] Furthermore, the present invention divides the structure of the boron nitride interface layer into three categories: amorphous, chaotic layer and hexagonal according to the length of the spin-lattice relaxation characteristic time T1 of the isotope B-11 of the boron nitride interface layer, wherein the hexagonal includes two types: incompletely crystallized hexagonal and completely crystallized hexagonal.

[0040] Specifically, when the spin-lattice relaxation characteristic time T1 is less than 0.1 s, the boron nitride interface layer has an amorphous structure.

[0041] Specifically, when the spin-lattice relaxation characteristic time T1 is 0.1-1.5 s, the boron nitride interface layer has a turbostratic structure.

[0042] Specifically, when the spin-lattice relaxation characteristic time T1 is 1.5-100 s, the boron nitride interface layer has an incompletely crystallized hexagonal structure; when the spin-lattice relaxation characteristic time T1>100 s, the boron nitride interface layer has a completely crystallized hexagonal structure.

[0043] The present invention uses the spin-lattice relaxation characteristic time T1 of B-11 to characterize the crystallinity of the interface layer of the ceramic-based composite material. Compared with the prior art, the present invention can accurately realize the quantitative characterization of the boron nitride interface layer of the composite material in a larger range; the microstructure of the boron nitride in the interface layer will affect the bonding between the bundled fibers and the matrix, determine the toughening effect of the bundled fibers, and thus affect the mechanical properties of the composite material. The use of the spin-lattice relaxation characteristic time T1 of the isotope B-11 can better guide the quality inspection of the composite material and optimize the material preparation process.

[0044] It should be noted that according to Thomas' definition of the crystallinity of hexagonal boron nitride, the graphitization index of hexagonal boron nitride that has reached complete graphitization is 1.6. The inventors have measured the commercial hexagonal boron nitride powder and found that the powder that meets the Thomas graphitization index of 1.6 has a spin-lattice relaxation characteristic time T1 of about 100s or longer. Therefore, the hexagonal boron nitride with a characteristic time of more than 100s is defined as completely crystallized (graphitized) boron nitride. During the measurement process, the inventors found that the spin-lattice relaxation characteristic time T1 of the measured turbostratic boron nitride was all above 0.1s, so the characteristic time 0.1s was defined as the dividing point between amorphous boron nitride and turbostratic boron nitride. For a boron nitride interface layer deposited on a heterogeneous substrate with a thickness of micrometers or hundreds of nanometers, a boron nitride interface layer with a characteristic time T1 value of 1.5s or longer can exert a good toughening effect. This relaxation characteristic time is taken as the dividing point between turbostratic boron nitride and incompletely crystallized (graphitized) hexagonal boron nitride.

[0045] Furthermore, when the spin-lattice relaxation characteristic time T1 of the isotope B-11 is greater than 1.5s, that is, when the crystallinity index is greater than 1.5, the boron nitride interface layer can play a good toughening effect in the ceramic matrix composite material. If the relaxation characteristic time is too short, it means that the crystallinity of the interface layer is insufficient, the layered structure grows poorly, the toughening effect is limited, and the material is brittle; but due to the existing preparation technology of the boron nitride interface layer, the relaxation characteristic time will not be too long, generally less than 100s.

[0046] It should be noted that the elastic strain of the silicon carbide ceramic matrix is ​​mostly around 0.05%, while the fracture strain of the bundled silicon carbide fiber can reach 1%. Usually, there should be a pseudoplastic section after the elastic section of the stress-strain curve of the ceramic matrix composite material. Only when the fracture strain of the composite material reaches more than 2 to 3 times the elastic strain of the matrix can it be considered that the bundled fiber and the interface layer have a good toughening effect.

[0047] It should be noted that solid-state nuclear magnetic resonance is a spectroscopic method for local atomic-level structure and motion analysis of specific types of atomic nuclei. It has the characteristics of not being interfered by other types of atomic nuclei, not destroying the structure of solid samples, and not damaging samples.

[0048] Furthermore, specifically, the present invention uses a solid-state nuclear magnetic resonance saturation-recovery method to measure the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer.

[0049] Specifically, the solid-state nuclear magnetic resonance saturation-recovery method includes: S1: preparing samples of the boron nitride interface layer of the ceramic matrix composite material; S2: collecting a solid nuclear magnetic resonance spectrum of the sample; S3: performing data fitting on the obtained spectrum to obtain the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer.

[0050] Specifically, in step S1, the bundled filaments with a boron nitride interface layer deposited on the surface of the ceramic matrix composite material can be ground with an agate mortar or cut with scissors to prepare powder or short fibers, and then loaded into a solid nuclear magnetic resonance ceramic rotor.

[0051] It is usually necessary to explain that the more disordered the local structure of the atomic nucleus is, the faster the change of its local magnetic field is, and the shorter the spin-lattice relaxation characteristic time T1 exhibited by the nuclear spin system is. Compared with liquid samples, the rapid movement of molecules in solid samples is restricted, resulting in various effects such as chemical shift anisotropy, which causes serious spectral line broadening. Therefore, the resolution of solid-state nuclear magnetic resonance technology is lower than that of liquids. In order to improve the resolution of solid-state nuclear magnetic resonance, magic angle spinning technology (MAS) is used to make the powder sample rotate rapidly to simulate the rapid movement of molecules in the solution, thereby reducing the factors that cause spectral line broadening.

[0052] Specifically, in step S2, when collecting the solid-state nuclear magnetic resonance spectrum of the sample, the ceramic rotor containing the boron nitride interface layer sample is placed in a solid-state nuclear magnetic resonance spectrometer, and the sample is subjected to rapid mechanical rotation around an axis at a magic angle (i.e., 54.74°) relative to the z-axis (magnetic field direction), thereby eliminating dipole-dipole and chemical shift anisotropic interactions to a great extent, improving the resolution of the solid-state nuclear magnetic resonance spectrum, and more accurately reflecting the structural composition of the interface layer boron nitride.

[0053] Furthermore, the present invention applies compressed air to blow the rotor blades to make the ceramic rotor rotate at a certain speed, wherein the magic angle rotation speed is 5~100kHz. If the speed is too low, it will not achieve the effect of eliminating the anisotropic effects in the solid; if the speed is too high, it will cause the speed or shaft to be unstable, and the rotor will touch the inner wall of the nuclear magnetic resonance probe, causing serious mechanical damage.

[0054] Specifically, the present invention adopts a single pulse test to collect a solid nuclear magnetic resonance spectrum of a boron nitride interface layer; and optimizes the test parameters to ensure that the boron-11 nuclear magnetic resonance signal of hexagonal boron nitride between 35 and 10 ppm can be collected. The solid nuclear magnetic resonance spectrum of the present invention is collected on a nuclear magnetic resonance spectrometer with a resonance frequency of 192.5 MHz for the boron-11 atomic nucleus. The obtained one-dimensional solid nuclear magnetic resonance spectrum of the boron nitride interface layer is as follows: Figure 2 shown.

[0055] Specifically, the present invention uses a series of very short intervals The saturation pulse makes the net magnetic moment in the magnetic field direction (z direction) approach 0. The pulse sequence used in the solid-state nuclear magnetic resonance saturation-recovery experiment of the present invention is as follows: Figure 1As shown; the effect of the saturation pulse sequence of the present invention should be based on the waiting time The nuclear magnetic signal collected when the value is zero is taken as zero, and the length of the single pulse, the interval time and the number of pulses are continuously optimized.

[0056] Furthermore, in order to improve the signal-to-noise ratio of nuclear magnetic resonance spectroscopy, the The number of saturation pulse sequences can be set to 50 to 200. Too many will increase the total time of the experiment and reduce the detection efficiency.

[0057] Furthermore, the boron nitride nuclear magnetic resonance spectrum was determined. The interval time of saturation pulse is 0.1~10ms. If the interval time is too short, the pulse emission component of the equipment will be subjected to high-power current for a long time, which may cause component damage; it will also heat the sample and affect the accuracy of the experimental results. If the interval time is too long, it will affect the saturation effect.

[0058] According to a preferred embodiment of the present invention, the boron nitride nuclear magnetic resonance spectrum is determined. The interval time of saturation pulse is 1ms.

[0059] Furthermore, the boron nitride nuclear magnetic resonance spectrum was determined. The length of the saturation pulse is 1~100μs. Based on the energy limitation of the device, the pulse length will not be too short; if the pulse length is too short, the excitation effect will be poor.

[0060] According to a preferred embodiment of the present invention, the boron nitride nuclear magnetic resonance spectrum is determined. The saturation pulse lengths are 1.73μs, 1.84μs, and 2.05μs, respectively.

[0061] Specifically, after a series of different waiting times After that, apply a certain interval Saturation pulse sequence and acquisition signal, for different waiting time The collected boron nitride signal is integrated or peaked to wait for a certain time. The horizontal axis is the peak area integral value or the reduced intensity of the peak value is the vertical axis. A curve that starts from 0 and increases exponentially and tends to be horizontal should be obtained. If the peak area or peak value does not reach the maximum value, a longer waiting time should be set. Repeat the test until a curve is obtained.

[0062] It should be noted that when the waiting time reaches about 3 times of T1, the signal strength collected by saturation recovery is restored to the level of direct application. Pulse and collect 95% of the signal intensity. Therefore, in order to accurately fit, the waiting time is set to at least 3 times or more of T1. When T1 is more than 100s, the structure of hexagonal boron nitride is in a completely crystallized state, but based on the limitations of the existing composite material interface layer preparation process and the requirements for composite material performance, the structure of the interface layer in the composite material is an incompletely crystallized hexagonal boron nitride structure, and T1 is in the range of 1.5s-100s, so the waiting time does not need to exceed 300s.

[0063] According to some preferred embodiments of the present invention, a series of waiting times are set. The waiting time is 1ms, 10ms, 100ms, 200ms, 400ms, 800ms, 1.2s, 1.6s, 2s, 4s, 6s, 8s, 12s, 16s, and 32s respectively. Data are collected and the hexagonal boron nitride signal between 35 and 10ppm is integrated. The maximum integral value is used as the denominator, and the other integral values ​​are divided by the maximum integral value for normalization to obtain a series of relative peak intensity data between 0 and 1. The horizontal axis is the horizontal axis, and the relative peak intensity is the vertical axis. The experimental results are shown in Figure 3 shown.

[0064] Specifically, in step S3, the peak area integral value minus the waiting time or peak-wait time A series of data points are fitted using the exponential decay function shown in formula (1): Formula (1) The value of characteristic time T1 is obtained by fitting; where I[ ] is the integral value or peak value under a specific waiting time; I[0] is a longer waiting time The saturation integral value or peak value reached under the condition; A is the pre-exponential factor, which is generated during the fitting process. Under ideal conditions, its value is -I[0], but in reality it often deviates from this value.

[0065] The present invention also provides a method for preparing a boron nitride interface layer in a ceramic-based composite material, the method comprising: (1) Preparing a boron nitride interface layer on the surface of the bundled fiber by chemical vapor deposition or chemical vapor infiltration process; (2) determining the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer; (3) Determine whether the relaxation characteristic time T1 measured in step (2) is within the range of >1.5s: If the conditions are met, continue to use the process described in step (1) to prepare boron nitride on the surface of the bundled fiber; If it does not meet the requirements, first change the process parameters of step (1), including temperature, pressure, and gas flow rate, and then prepare a boron nitride interface layer on the surface of the bundled filament fiber; (4) Repeat steps (2) to (3) until the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer meets the requirements.

[0066] Specifically, in step (1), a chemical vapor deposition (CVD) or chemical vapor infiltration (CVI) process is usually used to prepare a boron nitride interface layer on the surface of the bundled fiber.

[0067] According to some preferred embodiments of the present invention, a boron nitride interface layer is deposited on the surface of the bundled fiber by a CVD method.

[0068] Furthermore, boron nitride interface layer is prepared on the surface of bundled SiC fiber by using boron trichloride (BCl3) and ammonia (NH3) or other common boron nitride precursor / precursor combination.

[0069] It should be noted that the thickness of the interface layer is one of the important indicators for considering the toughening and protective performance of the bundled fibers and the interface layer on the composite material.

[0070] According to some preferred embodiments of the present invention, the thickness of the interface layer is 50nm~5μm. If the thickness is too small, the toughening effect will be insufficient and the composite material will be brittle; if the thickness is too large, the interface layer of the material will be too weak, the load cannot be effectively transferred from the matrix to the fiber, and the strength of the composite material will be low.

[0071] Specifically, in step (2), the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer can be determined by solid-state nuclear magnetic resonance saturation-recovery method. The specific process steps and parameter limitations are as described above and will not be repeated here.

[0072] Specifically, in step (3), it is determined whether the relaxation characteristic time T1 of the boron nitride interface layer measured in step (2) meets the requirements. If so, the chemical vapor deposition process described in step (1) is continued to be used to prepare boron nitride on the surface of the bundled fiber, and then the bundled fiber with the obtained surface coated with the boron nitride interface layer is uniformly distributed inside the ceramic matrix.

[0073] According to a preferred embodiment of the present invention, it is determined whether the relaxation characteristic time T1 measured in step (2) is within a range of >1.5 s.

[0074] According to a preferred embodiment of the present invention, a ceramic matrix composite material is prepared by a prepreg-melt infiltration process, and the specific steps include: The bundled fiber with a boron nitride interface layer on the surface is subjected to a chemical vapor deposition process to prepare a silicon carbide protective layer, and is pre-impregnated to form a fiber unidirectional tape; the fiber unidirectional tape is laid at 0° / 90°, hot-pressed and carbonized at high temperature, and finally reacted with molten silicon in a high temperature and vacuum environment to obtain a SiC / SiC composite material.

[0075] In some preferred embodiments of the present invention, the deposition, prepreg, hot pressing, carbonization, infiltration and other processes used are all traditional processes, and no special requirements are made on the process parameters.

[0076] Specifically, if the relaxation characteristic time T1 of the boron nitride interface layer measured in step (2) does not meet the requirements, first change the process parameters of step (1), including temperature, pressure, and gas flow rate, and then prepare the boron nitride interface layer on the surface of the bundled fiber.

[0077] According to some preferred embodiments of the present invention, when the measured relaxation characteristic time T1 of the boron nitride interface layer is 1.4 s, which does not meet the requirement of >1.5 s, the temperature and pressure of the chemical vapor deposition process in step (1) are changed to improve the structure of the boron nitride interface layer.

[0078] Specifically, in step (4), steps (2) to (3) are repeated until the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer meets the requirements, and then the subsequent preparation process of the composite material is carried out.

[0079] Furthermore, in order to protect the interface between the bundled filament fibers and the boron nitride, a protective layer is attached to the surface of the boron nitride interface layer in the present invention.

[0080] It should be noted that, compared with existing characterization methods such as TEM and Raman, after the surface of the boron nitride interface layer is coated with silicon carbide or silicon nitride coating, the spin-lattice relaxation characteristic time T1 of the isotope B-11 can also be used to quantitatively characterize the composite material.

[0081] Furthermore, the ceramic matrix is ​​a SiC matrix, the bundled fibers are bundled SiC fibers, and the protective layer is a silicon carbide and / or silicon nitride coating.

[0082] Specifically, according to the needs of SiC / SiC composite materials for specific purposes, the deposition process parameters such as temperature, pressure, and gas flow rate are changed, and a series of experiments are conducted to determine the characteristic time T1 of the boron nitride interface layer and make a table so that it can be selected in combination with the actual process requirements when used. Because the chemical vapor deposition effect is greatly affected by the process parameters, equipment structure, and substrate surface state, the product needs to be sampled in daily production to ensure that its crystallinity index falls within the applicable range.

[0083] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0084] Example 1 A boron nitride interface layer 1 is deposited on a bundled silicon carbide fiber with a diameter of 12 μm by chemical vapor deposition, wherein the deposition chamber size is Φ300 mm×500 mm, the reaction temperature is 900°C, the pressure is 200 Pa, the BCl3 flow rate is 0.1 L / min, the NH3 flow rate is 1 L / min, the hydrogen flow rate is 3 L / min, the deposition time is 20 min, and the thickness of the obtained interface layer is 0.5 μm.

[0085] The solid-state NMR spectrum of the boron nitride of the interface layer 1 was collected using a sample tube with a resonance frequency of 192.5 MHz for the boron-11 nucleus, a diameter of 4 mm, and a corresponding type of probe. The magic angle rotation speed of the sample tube was 12 kHz. Figure 1 The pulse sequence shown was used for saturation recovery test, where n=100 for saturation pulse sequence and the pulse interval was 1ms; (90°) pulse length 1.73μs; Set the series wait time The waiting time is 1ms, 10ms, 100ms, 200ms, 400ms, 800ms, 1.2s, 1.6s, 2s, 4s, 6s, 8s, 12s, 16s, and 32s respectively; collect data, and integrate the hexagonal boron nitride signal between 35 and 10ppm, with the largest integral value as the denominator, and divide the other integral values ​​by the maximum integral value for normalization to obtain a series of relative peak intensity data between 0 and 1. The horizontal axis is the horizontal axis, and the relative peak intensity is the vertical axis. The experimental results are shown in Figure 3 As shown by the hollow dots in (a); The experimental data were fitted using an exponential decay function (i.e., formula (1)), and the spin-lattice relaxation characteristic time T1 = 1.40 s, A = -0.985, R 2 The value is 0.998, which means that the experimental data is more consistent with the exponential decay function. The fitting curve is as follows Figure 3 Indicated by the dotted line in (a).

[0086] SiC / SiC composites were prepared by prepreg-melt infiltration process.

[0087] The tensile properties of SiC / SiC composites are shown in Table 1 and Figure 4 (a); As shown in Table 1, the ultimate tensile strength of the material is 137MPa, the elongation at break is 0.081%, the proportional limit is 125MPa, and the tensile modulus is 248GPa; Figure 4From the stress-curve of (a), it can be seen that the boron nitride interface layer at the characteristic time T1=1.40s can hardly achieve the toughening effect, and the material is almost brittle fracture; this indicates that the crystallinity of the boron nitride interface layer structure obtained by using the chemical vapor deposition parameters of Example 1 is low and cannot meet the requirements of the subsequent preparation of the composite material for the structure and performance of the boron nitride interface layer.

[0088] Example 2 On the basis of Example 1, the chemical vapor deposition process parameters were changed, specifically, the reaction temperature was adjusted to 1100° C., and the reaction pressure was adjusted to 100 Pa, and other conditions remained unchanged, to obtain a boron nitride interface layer 2; The solid-state NMR spectrum of the interface layer 2 boron nitride was collected using a 192.5 MHz resonance frequency of the boron-11 nucleus, a 4 mm diameter sample tube and a corresponding type of probe, and a magic angle rotation speed of 12 kHz for the sample tube; Figure 1 The pulse sequence shown was used for saturation recovery test, where n=100 for saturation pulse sequence and the pulse interval was 1ms; (90°) pulse length 1.84μs; Set the series wait time The waiting time is 1ms, 10ms, 100ms, 200ms, 400ms, 800ms, 1.2s, 1.6s, 2s, 4s, 6s, 8s, 12s, 16s, and 32s respectively; collect data, and integrate the hexagonal boron nitride signal between 35 and 10ppm, with the largest integral value as the denominator, and divide the other integral values ​​by the maximum integral value for normalization to obtain a series of relative peak intensity data between 0 and 1. The horizontal axis is the horizontal axis, and the relative peak intensity is the vertical axis. The experimental results are shown in Figure 3 As shown by the hollow dots in (b); The experimental data were fitted with an exponential decay function (i.e., formula (1)), and the spin-lattice relaxation characteristic time T1 = 1.71 s, A = -0.960, R 2 The value is 0.999, which means that the experimental data is more consistent with the exponential decay function. The fitting curve is as follows Figure 3 (b) is shown by the dotted line.

[0089] SiC / SiC composites were prepared by prepreg-melt infiltration process.

[0090] The tensile properties of SiC / SiC composites are shown in Table 1 and Figure 4(b); As shown in Table 1, it can be seen that by adjusting the chemical vapor deposition parameters in Example 2 on the basis of Example 1, the crystallinity of the structure of the obtained boron nitride interface layer 2 becomes higher, and the mechanical properties of the material are also improved, with an ultimate tensile strength of 198 MPa, an elongation at break of 0.176%, a proportional limit of 126 MPa, and a tensile modulus of 216 GPa; and from Figure 4 From the stress-curve of (b), it can be seen that the boron nitride interface layer with the characteristic time T1=1.71s has a certain toughening effect. After the elastic section where the matrix bears the load, there is a certain amount of fiber pullout, which meets the requirements of the subsequent preparation of composite materials for the structure and performance of the boron nitride interface layer.

[0091] Example 3 On the basis of Example 2, the chemical vapor deposition process parameters are further adjusted. Specifically, the reaction temperature is adjusted to 1300° C., and the reaction pressure is adjusted to 50 Pa. Other conditions remain unchanged to obtain a boron nitride interface layer 3. The solid-state NMR spectrum of the interface layer 3 boron nitride was collected using a sample tube with a resonance frequency of 192.5 MHz for the boron-11 nucleus, a diameter of 4 mm, and a corresponding type of probe. The magic angle rotation speed of the sample tube was 12 kHz. Figure 1 The pulse sequence shown was used for saturation recovery test, where n=100 for saturation pulse sequence and the pulse interval was 1ms; (90°) pulse length 2.05μs; Set the series wait time The waiting time is 1ms, 10ms, 100ms, 200ms, 400ms, 800ms, 1.2s, 1.6s, 2s, 4s, 6s, 8s, 12s, 16s, and 32s respectively; collect data, and integrate the hexagonal boron nitride signal between 35 and 10ppm, with the largest integral value as the denominator, and divide the other integral values ​​by the maximum integral value for normalization to obtain a series of relative peak intensity data between 0 and 1. The horizontal axis is the horizontal axis, and the relative peak intensity is the vertical axis. The experimental results are shown in Figure 3 As shown by the hollow dots in (c); The experimental data were fitted with an exponential decay function (i.e., formula (1)), and the spin-lattice relaxation characteristic time T1 = 3.24 s, A = -0.960, R 2 The value is 0.997, indicating that the experimental data is more consistent with the exponential decay function. The fitting curve is as follows Figure 3 (c) is shown by the dotted line.

[0092] SiC / SiC composites were prepared by prepreg-melt infiltration process.

[0093] The tensile properties of SiC / SiC composites are shown in Table 1 and Figure 4 (c); As shown in Table 1, it can be seen that by adjusting the chemical vapor deposition parameters in Example 3 on the basis of Example 2, the crystallinity of the structure of the obtained boron nitride interface layer 3 becomes higher, and the mechanical properties of the material are further improved. The ultimate tensile strength of the material is 233 MPa, the elongation at break is 0.336%, the proportional limit is 126 MPa, and the tensile modulus is 212 GPa; Figure 4 From the stress-curve of (c), it can be seen that the boron nitride interface layer with the characteristic time T1=3.24s has a good toughening effect and an obvious fiber pull-out effect. The composite material exhibits good toughness and better meets the requirements of the subsequent preparation of the composite material for the structure and performance of the boron nitride interface layer.

[0094] Table 1

[0095] Verification example: The boron nitride interface layers 1-3 prepared in Examples 1-3 were tested and analyzed using TEM. The test results are as follows: Figure 5 As shown in (a)~(c), it can be seen that: The interface layer 1 prepared in Example 1 is a whole layer of turbostratic boron nitride, with vortex lattice fringes of small grains, more amorphous regions between grains, and a grain size of L c Generally less than 2nm, (002) plane interlayer spacing is about 0.349nm, significantly higher than the ideal interlayer spacing of hexagonal boron nitride 0.333nm. Smaller grain size, larger interlayer spacing, more amorphous regions, and vortex-shaped lattice fringes all indicate that the crystallinity of the boron nitride interface layer in this embodiment is poor, and it is a chaotic layer boron nitride.

[0096] The lattice stripes of the interface layer 2 prepared in Example 2 tend to be straight as a whole, the amorphous area is relatively reduced, and the maximum grain size L c It can reach about 5nm, and the (002) interlayer spacing is about 0.346nm. The whole can be considered as incompletely crystallized hexagonal boron nitride.

[0097] The lattice stripes of the interface layer prepared in Example 3 are generally consistent in direction, and there is almost no amorphous region. The maximum grain size L c It can reach 10nm, and the (002) plane interlayer spacing is about 0.335nm, which is very close to the theoretical value of 0.333nm of the (002) plane interlayer spacing of hexagonal boron nitride. Although it is still an incompletely crystallized hexagonal boron nitride, its crystallinity is significantly higher than that of the hexagonal boron nitride in Example 2.

[0098] It can be seen that the present invention uses the B-11 spin-lattice relaxation characteristic time T1 to characterize the crystallinity of the boron nitride interface layer, which can correctly reflect the microstructure of the boron nitride interface layer and achieve quantitative characterization of the boron nitride interface layer of the composite material.

[0099] Compared with the current TEM test method, the present invention can more accurately and quickly obtain the structural information of the boron nitride interface layer by measuring the B-11 spin-lattice relaxation characteristic time in the boron nitride interface layer, and give the overall crystallinity of the crystal layer, which can reflect the average structural state of a large number of samples; in addition, the use of solid nuclear magnetic resonance to measure the spin-lattice relaxation characteristic time will not destroy the solid sample structure, will not damage the sample, and will reduce time and economic costs, which is conducive to controlling the quality of composite materials and guiding the material preparation process. Although the TEM analysis method is very intuitive, the observation area each time is only tens of square microns, which can only represent the crystallinity of the interface layer of a specific cross section of a single fiber bundle. For the boron nitride interface layer on a bundle of filament fibers, a large number of tests are required to obtain the overall structural information of the boron nitride interface layer, and the test cost is high and the test time is long, which is not suitable for application in actual production.

[0100] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for characterizing the crystallinity of a boron nitride interface layer of a ceramic matrix composite material, characterized in that: The method comprises: The spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer is measured by solid-state nuclear magnetic resonance method; Determining the crystallinity of the boron nitride interface layer according to the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer; The composite material includes a ceramic matrix and bundled filament fibers dispersed therein, and the boron nitride interface layer is attached to the surface of the bundled filament fibers.

2. The method according to claim 1, characterized in that The structure of the boron nitride interface layer is determined according to the value of the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer, and the crystallinity of the boron nitride interface layer is expressed by the structure of the boron nitride interface layer.

3. The method according to claim 2, characterized in that When T1<0.1s, the boron nitride interface layer has an amorphous structure; When T1 is 0.1-1.5s, the boron nitride interface layer has a turbostratic structure; When T1 is 1.5-100s, the boron nitride interface layer has an incompletely crystallized hexagonal structure; When T1>100s, the boron nitride interface layer has a completely crystallized hexagonal structure.

4. The method according to claim 1, characterized in that The method for measuring the spin-lattice relaxation characteristic time T1 of the isotope B-11 comprises: S1: preparing a sample of a boron nitride interface layer of a ceramic matrix composite material to obtain a sample; S2: collecting a solid nuclear magnetic resonance spectrum of the sample; S3: performing data fitting on the obtained spectrum to obtain the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer.

5. The method according to claim 4, characterized in that The spin-lattice relaxation characteristic time T1 of isotope B-11 was measured by solid-state NMR saturation-recovery method.

6. The method according to claim 5, characterized in that In step S2, the sample is subjected to magic angle rotation, and the rotation speed of the magic angle rotation is 5-100 kHz; The number of saturation pulses is 50~200, the pulse length is 1~100μm, the interval time is 0.1~10ms, and the waiting time is 1ms~300s.

7. A method for preparing a boron nitride interface layer in a ceramic matrix composite material, characterized in that: The method comprises: (1) Preparing a boron nitride interface layer on the surface of the bundled fiber by chemical vapor deposition or chemical vapor infiltration process; (2) determining the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer; (3) Determine whether the relaxation characteristic time T1 measured in step (2) is within the range of >1.5s: If the conditions are met, continue to use the process described in step (1) to prepare boron nitride on the surface of the bundled fiber; If it does not meet the requirements, first change the process parameters of step (1), including temperature, pressure, and gas flow rate, and then prepare a boron nitride interface layer on the surface of the bundled filament fiber; (4) Repeat steps (2) to (3) until the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer meets the requirements.

8. The preparation method according to claim 7, characterized in that: In step (1), the thickness of the boron nitride interface layer is 50 nm to 5 μm.

9. The preparation method according to claim 7, characterized in that: In step (2), the spin-lattice relaxation characteristic time T1 of the isotope B-11 in the boron nitride interface layer is measured by solid-state nuclear magnetic resonance saturation-recovery method, wherein in the measurement, the sample is subjected to magic angle rotation at a rotation speed of 5 to 100 kHz. The number of saturation pulses is 50~200, and the interval time is 0.1~10ms.

10. The preparation method according to claim 7, characterized in that: The bundled filament fibers are bundled filament SiC fibers.

Citation Information

Patent Citations

  • Lithium ion conductive sulfide-based solid electrolyte and all-solid lithium battery using same

    CN101326673A

  • Polishing pad and manufacturing method therefor

    CN103563056A

  • Sheet-shaped alumina particles and method for producing sheet-shaped alumina particles

    CN114514290A

  • Method determining degree of crystallinity of natural polymers

    RU2175765C1